Profil Sheikh Sulaiman Ar-Rasuli (1871 M – 1970 M) sebagai Pendakwah - Sarwan Sarwan (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2012)
Sheikh Sulaiman Ar-Rasuli is a proselytizer who is from proselytizers generation. He has got Islamic education well either national or international. He is the old proselytizer  that persevering defense ahlussunnah wal jamaah and mazhab Syafi’i  faith. He gives Islamic preaching orally, written, and actions